Pancreatic Neuroendocrine Microtumors (WHO 2022) Are Not Always Low-Grade Neoplasms: A Case with a Highly Increased Proliferation Rate - Chouchane, Aziz; Kirchner, Philipp; Marinoni, Ilaria; Sticová, Eva; Jirásek, Tomáš; Perren, Aurel (Endocrine pathology, 2024)
Traditionally considered non-functional low proliferative benign neuroendocrine proliferations measuring less than 5 mm, pancreatic (neuro)endocrine microadenomas are now classified as pancreatic neuroendocrine microtumors in the 2022 WHO classification of endocrine and neuroendocrine tumors. This case report discussed the features of an incidentally identified 4.7-mm glucagon-expressing pancreatic neuroendocrine microtumor with MEN1 mutation only, chromosomally stable and an epigenetic alpha-like phenotype. The tumor was associated with an unexplained increased proliferation rate in Ki-67 of 15%. There was no associated DAXX/ATRX deficiency. The presented case challenges the conventional thought of a low proliferative disease of the so-called "pancreatic neuroendocrine microadenomas" and provides additional support to the 2022 WHO classification that also requires grading of these neoplasms. Despite exhibiting molecular features of less aggressive behavior, the case also underscores the biological complexity of pancreatic neuroendocrine microtumors. By recognizing the heterogenous spectrum of neuroendocrine neoplasms, the current case also contributes to ongoing discussions on how to optimize the clinical management of such tumors.
Keywords: Microadenoma; Pancreatic neuroendocrine microtumors; Neoplasm Grading; Middle Aged; Neuroendocrine Tumors; Proto-Oncogene Proteins; nádory slinivky břišní; Cell Proliferation; MEN1; Neuroendocrine neoplasm; Humans; Pancreatic Neoplasms; WHO 2022; PanNETs; protoonkogenní proteiny; lidé středního věku; stupeň nádoru; proliferace buněk; neuroendokrinní nádory; lidé; Ki-67